PELAKSANAAN DIGITALISASI PELAYANAN PADA WEBSITE “SIPENDUK ONLINE” DI DISDUKCAPIL KABUPATEN SEMARANG - Ramadhani, Shinta Putri; -, Yuwanto -; Marlina, Neny - (Journal of Politic and Government Studies, 2024)
This research discusses the digitalization of services on the